Kirschner wires versus cannulated screws for hallux valgus correction (bunion) through the minimally invasive Chevron-Akin technique: A two-year randomized controlled trial - Vieira Sampaio, Wagner; Pinheiro da Silva, Maria Clara; Alencar Mendes de Carvalho, Kepler; de Almeida Lemos, Arthur Cláudio; Ramos Maradei Pereira, João Alberto; Malheiros Luzo, Marcus Vinicius (Journal of the Foot & Ankle, 2026)
Introduction: Hallux valgus (HV) is a painful lateral deviation of the great toe and medial deviation of the first metatarsal of the foot, affecting almost 20% of the general population. Minimally invasive surgery can correct the deformity using cannulated screws or Kirschner wires. This trial evaluated the efficacy and safety of the two fixation methods with a two-year follow-up. Methods: This was a randomized, open and parallel clinical trial, conducted in a single orthopedic hospital, with a superiority framework. We randomized 40 adult patients with moderate to severe HV to be operated on using K-wires or cannulated screws for fixation. Patients allocated to K-wires group returned in six weeks for wire removal (which prevented blinding). We evaluated function and radiographic HV correction as primary outcomes, and pain, satisfaction, degenerative changes in two years, and adverse effects secondarily. Brazilian Registry of Clinical Trials (ReBEC) RBR-107ynv85. Results: From 2021 to 2022, 64 patients were admitted for HV surgery and 40 were randomized. We lost 6 patients for follow-up, 3 in each group. All radiographic outcomes changed positively across time, with no significant difference between groups. Function and pain scores also improved, with function scores higher in the K-wires group at 6, 12, and 24 months (p < 0.001). There was no relevant degeneration at 24 months. Of the 7 adverse events registered, 6 were in the cannulated screws group. Conclusions: No significant difference was found between the two implants regarding clinical, radiographic, safety, functional, and late degenerative outcomes.